Heterogeneous Integration of Carbon‐Nanotube–Graphene for High‐Performance, Flexible, and Transparent Photodetectors. Issue 27 (24th May 2017) - Pyo, Soonjae; Kim, Wondo; Jung, Han‐Il; Choi, Jungwook; Kim, Jongbaeg
Abstract : Low‐dimensional carbon materials, such as semiconducting carbon nanotubes (CNTs), conducting graphene, and their hybrids, are of great interest as promising candidates for flexible, foldable, and transparent electronics. However, the development of highly photoresponsive, flexible, and transparent optoelectronics still remains limited due to their low absorbance and fast recombination rate of photoexcited charges, despite the considerable potential of photodetectors for future wearable and foldable devices. This work demonstrates a heterogeneous, all‐carbon photodetector composed of graphene electrodes and porphyrin‐interfaced single‐walled CNTs (SWNTs) channel, exhibiting high photoresponse, flexibility, and full transparency across the device. The porphyrin molecules generate and transfer photoexcited holes to the SWNTs even under weak white light, resulting in significant improvement of photoresponsivity from negligible to 1.6 × 10 −2 A W −1 . Simultaneously, the photodetector exhibits high flexibility allowing stable light detection under ≈50% strain (i.e., a bending radius of ≈350 µm), and retaining a sufficient transparency of ≈80% at 550 nm. Experimental demonstrations as a wearable sunlight sensor highlight the utility of the photodetector that can be conformally mounted on human skin and other curved surfaces without any mechanical and optical constraints. The heterogeneous integration of porphyrin–SWNT–graphene may provide a viable route to produce invisible, high‐performance optoelectronic systems. Abstract : Flexible and transparent photodetectors based on porphyrin–single‐walled carbon nanotube (SWNT)–graphene heterostructures are presented. The heterogeneous integration of an SWNT channel and graphene electrode provides remarkable electrical contact and mechanical robustness, with high transparency. The porphyrin greatly improves weak photoresponse of carbon nanomaterials, while preserving flexibility and transparency. Potential utility of the photodetector as a wearable sunlight sensor is demonstrated.